Supervisi Akademik Berkelanjutan Dapat Meningkatkan Kompetensi Guru dalam Menyusun Silabus dan RPP di SMPN 6 Bathin Solapan - Tati Wijaya (Departement of Mathematics Education, 2022)
This research was conducted from March to April 2022. This research aims to provide benefits for school principals as researchers in solving the problems of students who arrive late and problems that are not appreciated, so that it becomes better and provides a conducive atmosphere at SMP Negeri 6 Bathin Solapan . The subjects of this research were teachers of SMP Negeri 6 Bathin Solapan. This research was conducted using classroom action research methods which lasted for 2 cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The research method used by researchers is to carry out academic supervision which includes traditional supervision and clinical supervision. The results show that continuous academic supervision has been scientifically proven to be able to increase teacher competence in preparing syllabus and lesson plans at SMP Negeri 6 Bathin Solapan. This is proven by the increase in the number of good teacher syllabuses from 31% to 83% after academic supervision. In addition, the number of good quality lesson plans also increased from 31% to 89%.